Profit and Local Culture in Pesantren: A Transcendental Phenomenology - Mohamad Anwar Thalib; Mohamad Akbar Ali; Nurjayanti Langgai (AKTIVA: Journal of Accountancy and Management, 2026)
Research Purpose: This study aims to explain how profit is conceptualized within the cultural and spiritual context of Islamic boarding schools (pesantren) in Gorontalo, Indonesia. Method: The study employs a transcendental phenomenology approach within the interpretive paradigm, using qualitative methods with purposive sampling of teachers at Hidayatullah Islamic Boarding School. Data were collected through in-depth interviews and analyzed using noema, epoche, noesis, intentional analysis, and eidetic reduction.Research Findings: The study reveals three dimensions of profit: (1) material profit, such as salary and allowances, viewed as appreciation for teachers' dedication; (2) non-material profit reflected in students’ achievements, which generate pride, happiness, and institutional value; and (3) transcendental profit, manifested in acts of worship believed to yield eternal rewards from Allah SWT. These meanings align with the Gorontalo local philosophy Diila o’onto, bo wolu-woluwo (unseen but present), combining material, social, and spiritual aspects.Novelty: This study contributes to the development of context-based accounting by demonstrating that profit in pesantren is holistic and culturally embedded. It offers a locally grounded model of teacher welfare and enriches the discourse of spiritual and cultural accounting in Indonesia.   Tujuan Penelitian: Penelitian ini bertujuan menjelaskan bagaimana laba dimaknai dalam konteks budaya dan spiritualitas pesantren di Gorontalo, Indonesia.Metode dan pendekatan: penelitian menggunakan pendekatan fenomenologi transendental dalam paradigma interpretif, dengan metode kualitatif dan pemilihan informan guru Pesantren Hidayatullah secara purposive. Data dikumpulkan melalui wawancara mendalam dan dianalisis melalui tahapan noema, epoche, noesis, analisis intensional, dan reduksi eidetik.Temuan Penelitian: Penelitian mengungkap tiga dimensi makna laba: (1) laba material berupa gaji dan tunjangan sebagai bentuk apresiasi; (2) laba non-materi berupa prestasi siswa yang menghadirkan kebanggaan, kebahagiaan, dan nilai tambah bagi institusi; serta (3) laba transendental berupa amal ibadah yang diyakini memberi pahala abadi dari Allah SWT. Makna ini mencerminkan falsafah lokal Gorontalo Diila o’onto, bo wolu-woluwo (yang tak terlihat namun hadir), yang menyatukan dimensi material, sosial, dan spiritual.Kontribusi: Penelitian ini memberikan kontribusi terhadap pengembangan akuntansi berbasis konteks lokal dengan menunjukkan bahwa laba di pesantren bersifat holistik dan terikat budaya. Studi ini menawarkan model kesejahteraan guru berbasis kearifan lokal dan memperkaya wacana akuntansi budaya dan spiritual di Indonesia.